Force Balance along Isunnguata Sermia, West Greenland - Meierbachtol, Toby; Harper, Joel; Johnson, Jesse (Frontiers in Earth Science, 2016)
Ice flows when gravity acts on gradients in surface elevation, producing driving stresses. In the Isunnguata Sermia and Russel Glacier catchments of western Greenland, a 50% decline in driving stress along a flow line is juxtaposed with increasing surface flow speed. Here, these circumstances are investigated using modern observational data sources and an analysis of the balance of forces. Stress gradients in the ice mass and basal drag which resist the local driving stress are computed in order to investigate the underlying processes influencing the velocity and stress regimes. Our results show that the largest resistive stress gradients along the flowline result from increasing surface velocity. However, the longitudinal coupling stresses fail to exceed 15 kPa, or 20% of the local driving stress. Consequently, computed basal drag declines in proportion to the driving stress. In the absence of significant resistive stress gradients, other mechanisms are therefore necessary to explain the observed velocity increase despite declining driving stress. In the study area, the observed velocity - driving stress feature occurs at the long-term mean position of the equilibrium line of surface mass balance. We hypothesize that this position approximates the inland limit where surface meltwater penetrates the bed, and that the increased surface velocity reflects enhanced basal motion associated with seasonal meltwater perturbations.